Design and Development of a Web-Based Integrated Health Post Application for Infants, Toddlers, and Pregnant Women at the Belida Darat Community Health Center - Merlianda Oktarina; Ariansyah; Muchlis (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Belida Darat Health Center is under the auspices of the Muara Enim Regency Health Office, this Health Center is located in Belida Darat District, precisely in Tanjung Bunut Village. Currently, Belida Darat Health Center does not have an application for managing data on infants, toddlers and pregnant women, so the purpose of this study is to build a posyandu application to facilitate the management of data on infants, toddlers and pregnant women at Belida Darat Health Center. The research method uses a qualitative descriptive method with data collection techniques in the form of observation, interviews and literature studies, data sources consist of primary data and secondary data. while for the system development method using the RAD (Rapid Application Development) method, the system design tool used is UML (unified modeling Language). The design of this application uses the PHP (Processor Hypertext) programming language, MySQL Database and Coding using Visual Studio Code.